The Cost Effectiveness of Polyetheretheketone (PEEK) Cages for Anterior Cervical Discectomy and Fusion. Issue 8 (October 2015) - Virk, Sohrab S.; Elder, J. Bradley; Sandhu, Harvinder S.; Khan, Safdar N.
Abstract : Study Design: Cost-effectiveness analysis using a Markov model with inputs from published literature. Objective: To learn which graft or hardware option used in a single-level anterior cervical discectomy and fusion (ACDF) is most beneficial in terms of cost, quality of life, and overall cost effectiveness. Options studied were autograft, allograft, and polyetheretherketone (PEEK) cages for cervical fusion. Summary of Background Data: ACDF is commonly used to treat cervical myelopathy and/or radiculopathy. No study has compared the cost effectiveness of autograft, allograft, and PEEK in 1-level ACDF. Materials and Methods: A literature review provided inputs into a Markov decision model to determine the most effective graft or hardware option for 1-level ACDF. Data regarding rate of complications, quality-adjusted life years (QALYs) gained, and cost for each procedure type was collected. The Markov model was first run in a base case, using all currently available data. The model was then tested using 1-way and 2-way sensitivity analyses to determine the validity of the model's conclusions if specific aspects of model were changed. This model was run for 10 years postoperatively. Results: The cost per QALY for each option in the base case analysis was $3328/QALY for PEEK, $2492/QALY for autograft, and $2492/QALY for allograft. All graft/hardware options are cost effective ways to improve outcomes for patients living with chronic neck pain. For graft/hardware options the most cost-effective option was allograft. The incremental cost-effectiveness ratio for PEEK compared with autograft or allograft was >$100, 000/QALY. Conclusions: Allograft is the most cost-effective graft/hardware option for ACDF. Compared with living with cervical myelopathy and/or radiculopathy, ACDF using any graft or hardware option is a cost-effective method of improving the quality of life of patients. PEEK is not a cost-effective option compared with allograft or autograft for use in ACDF.